2002
DOI: 10.1124/jpet.302.2.416
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of the HumanCYP2A13Gene: Identification of Single-Nucleotide Polymorphisms and Functional Characterization of an Arg257Cys Variant

Abstract: Human cytochrome P450 2A13 (CYP2A13), which is highly efficient in the metabolic activation of a major tobacco-specific carcinogen, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), may play important roles in xenobiotic toxicity and tobacco-related tumorigenesis in the respiratory tract. The aim of this study was to identify any genetic polymorphisms of the CYP2A13 gene, which may alter the metabolic capacities of the enzyme. Polymerase chain reaction (PCR) single-strand conformational polymorphism analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
70
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 35 publications
(35 reference statements)
11
70
4
Order By: Relevance
“…Among the CYP genes examined here, other investigators have previously detected 27 polymorphisms that would affect amino acid sequences [ten in CYP2A6, six in CYP2B6, three in CYP2E, and eight in TBXAS1; Human Cytochrome P450 (CYP) Allele Nomenclature Committee, http://www.imm.ki.se/CYPalleles/]. Zhang et al (2002) have detected an additional SNP (Arg257-Cys) in the coding region of CYP2A13. However, of the 28 polymorphisms reported previously, we have found only six in our Japanese population sample (Ile471Thr in CYP2A6; Arg257Cys in CYP2A13; Arg22Cys, Gln172His, and Arg487Cys in CYP2B6; Glu450Lys in TBXAS1).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Among the CYP genes examined here, other investigators have previously detected 27 polymorphisms that would affect amino acid sequences [ten in CYP2A6, six in CYP2B6, three in CYP2E, and eight in TBXAS1; Human Cytochrome P450 (CYP) Allele Nomenclature Committee, http://www.imm.ki.se/CYPalleles/]. Zhang et al (2002) have detected an additional SNP (Arg257-Cys) in the coding region of CYP2A13. However, of the 28 polymorphisms reported previously, we have found only six in our Japanese population sample (Ile471Thr in CYP2A6; Arg257Cys in CYP2A13; Arg22Cys, Gln172His, and Arg487Cys in CYP2B6; Glu450Lys in TBXAS1).…”
Section: Discussionmentioning
confidence: 90%
“…Open boxes Exons, hatching unsequenced regions of repetitive elements, ATG initiation codon, TGA, TAG stop codons Ariyoshi et al (2001) c SNP previously reported by Zhang et al (2002) d SNP previously reported by Lang et al (2001) e SNPs previously reported by Fairbrother et al (1998) f SNP previously reported by Baek et al (1996) g SNP previously reported by Chevalier et al (2001) Gene and variation no. …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, we and other groups have documented that the interaction of CYP2A13 and NNK is associated with lung cancer. 4,10,11 In addition, we previously analyzed the possible association between lung cancer and variants of the b-2 adrenergic receptor gene ADRB2, which is the key mediator of the NNK nongenotoxic pathway. 12 It also has been reported that polymorphisms in the phase II conjugation enzyme genes, such as uridine diphosphate glucuronosyltransferase 1 family, polypeptide A7 (UGT1A7) and UGT2B17, have implications in lung cancer etiology.…”
mentioning
confidence: 99%
“…These substitutions can affect substrate specificity or metabolic turnover of the CYP2A13 enzyme. However, functional differences in the SNP variants of CYP2A13 are limited; the studies using recombinant proteins expressed in mammalian cell cultures showed that the CYP2A13*4 protein has decreased metabolic activity on NNK and aflatoxin B1, and that the CYP2A13*2 protein is less efficient in metabolic activation of NNK than wild-type CYP2A13*1 (Zhang et al, 2002;Wang et al, 2003Wang et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%